Math, asked by nakshatrasrujana, 9 days ago

p(x)=xsquare+5x-4 then find p(1)-p(-1)​

Answers

Answered by bhanuprakash814379
1

Step-by-step explanation:

p(1) = (1)^2+5(1)-4

= 1+5-4 = 2

p(-1) = (-1)^2 + 5(-1)-4

= 1-5-4

=-8

p(1)-p(-1) = 2-(-8) = 2+8=10

Answered by vanshgaur789
2

Step-by-step explanation:

x²+ 5x -4

i) p(1) = x=1

x²+ 5x -4

1² +5*1 -4

1 + 5 -4

6-4 =2

p(1) =2

ii) p(-1) = x= -1

x²+ 5x -4

(-1)² + 5(-1) -4

1 -5 -4

= 1-9

= -8

so (p1)- (p-1)

2 - (-8)

2+8

=10

plz mark it brainliest answer

Similar questions